Odpowiedzi

2009-11-29T20:33:41+01:00
Wyraz osmy+wyraz trzynasty=37
wyraz dziewiaty-wyraz szosty=9

wyraz osmy=wyraz pierwszy+7r
wyraz trzynasty=wyraz pierwszy+12r
wyraz dziewiaty=wyraz pierwszy+8r
wyraz szosty=wyraz pierwszy+5r

(wyraz pierwszy+7r)+(wyraz pierwszy+12r)=37
{
(wyraz pierwszy+8r)-(wyraz pierwszy+5r)=9

wyraz pierwszy+7r+wyraz pierwszy+12r=37
{
wyraz pierwszy+8r-wyraz pierwszy-5r=9

2wyrazu pierwszego+19r=37
{
3r=9 /:3

r=3

2pierwszego wyrazu=37-(19*3)
2pierwszego wyrazu=37-57
2pierwszego wyrazu=-20 /2
pierwszy wyraz= -10